CT-GUIDED PERCUTANEOUS FIXATION OF PELVIC FRACTURES. CASE REPORTS - Chmelová, Jana; Šír, Milan; Ječmínek, Vladimír (Biomedical papers, 2005)
Unstable pelvic fractures are usually associated with high impact energy trauma. As to surgical procedures the most frequently used methods are open reduction and inner fixation (ORIF), the other methods of stabilizing the unstable posterior pelvic ring are percutaneous iliosacral screw fixation under fluoroscopic control and CT-guided percutaneous fixation. The last mentioned procedure eliminates some of the problems associated with surgical treatment: prevents excessive blood loss during manipulation of the fracture hematom, lowers the possibility of infection, allows more accurate screw placement with direct measuring of the screw length and decreases the possibility of nerve injury. The CT-guided fixation is a delicate procedure and its result depends among others on the cooperation between operating room and CT room personnel. The radiologist and CT technologist have to know the operation technique and have to understand surgeon's requirements. In the available literature only a little was written and mentioned about the exact role of radiologist and CT technologist in the team. The aim of this article is to present the operation technique according to authors' own experience with two operated patients and to mention the surgeon's requirements on CT team.
Keywords: Pelvic fracture/Percutaneous fixation/CT-guided surgery